ESTIMVIS: un sistema computarizado para estimulación visual - Guevara Pérez, Miguel Ángel; Sanz-Martín, Araceli; Hernández-González, Marisela; Ramos-Loyo, Julieta (Revista Mexicana de Ingenieria Biomedica, 2004)
The necessity of cognitive sciences of presenting stimuli in a precise way and of evaluating subjects’ performance objectively, has motivated the creation of computer stimulation systems. This work describes the functioning and advantages of ESTIMVIS, a computer program designed to present visual and auditory stimuli, which can be executed in computers with minimum hardware requirements. ESTIMVIS allows the presentation of many kind of images, the precise control of the time and form of the stimuli presentation, the implementation of many stimulation paradigms, as well as the recording of the kind of response and the reaction time of the subject. The program, also, generates pulses related to the stimuli presentation, that can be sent to another computer in order to synchronically trigger brain electrical activity recordings (EEG and ERPs). ESTIMVIS has been used in several investigations for studying processes such as selective attention and emotion recognition in normal and schizophrenic populations